Toxicological evaluation of standardized Kaempferia parviflora extract: Sub-chronic and mutagenicity studies. (2019) - Yoshino, Susumu; Awa, Riyo; Ohto, Nobuaki; Miyake, Yasuo; Kuwahara, Hiroshige
Highlights: Kaempferia parviflora extract exhibited no genotoxicity. The no-observed-adverse-effect-level (NOAEL) of the extract was > 249 mg/kg. Our results indicate that Kaempferia parviflora extract has a high degree of safety. Abstract: Kaempferia parviflora (KP), also known as Krachai-dam in Thailand, belongs to the family Zingiberaceae and has been used traditionally to improve blood flow and treat inflammatory, allergic, and gastrointestinal disorders. The objective of this study was to investigate the safety profile of a standardized hydroalcoholic KP rhizome extract via mutagenicity and sub-chronic toxicity evaluations using in vitro and in vivo techniques. The in vitro mutagenicity of KP extract was assessed via reverse mutation tests using Salmonella typhimurium TA98, TA100, TA1535, and TA1537, and Escherichia coli WP2 uvrA . The sub-chronic toxicity profile was evaluated after daily oral administration of KP extract to Sprague-Dawley rats for 90 days. General toxicological parameters were monitored weekly. After the treatment period, blood was collected for hematological and biochemical analyses and certain organs were removed for macroscopic and histopathological analyses. Reverse mutation tests revealed that KP extract did not induce gene mutations at any of the concentrations tested. In the sub-chronic toxicity test, a few changes were observed, including increased salivation in the animals administered high-dose KP extract (249 mg/kg body weight (bw)/day). No toxicologically relevant changes were observed in the biochemical analysis. Sub-chronic administration of KP extract increased platelet levels in animals administered low-dose KP extract (25 mg/kg bw/day). However, the hematological and biochemical parameters remained within normal physiological ranges for the animal species. No toxicological changes were observed in the macroscopic and histopathological analyses performed in this study. These results demonstrate that KP extract is not genotoxic and that 90-day oral administration of the doses tested did not result in toxicity. Therefore, KP extract has a high safety margin for daily use.